Psychological Wellbeing and Coping Strategies of University Students with Physical Disability (Journal of Science and Technology, 2024)
Objective: University education can be challenging and students with disabilities (SWDs) have the added disadvantage of disability as a potential source of distress. This study examined the psychological well-being of students with physical disabilities at the Kwame Nkrumah University of Science and Technology (KNUST) and how they cope.Method: This was a cross-sectional study using the Depression, Anxiety, Stress Scale (DASS-21) and Brief COPE assessment tools to assess psychological distress and coping mechanisms among KNUST students with physical disabilities. Descriptive analyses, including correlations, were performed to examine the associations between well-being indices and coping variables.Results: Forty-five (45) students participated in the study. The mean age was 23 years (SD±2.96) and 77.8% of them were male students. Approximately 31.1% of the students experiencedm moderate to severe stress, 42.2% experienced moderate to extremely severe depression, and 46.7% experienced moderate to extremely severe anxiety. Emotion focused coping style was the most highly used among the students followed by problem-focused, then avoidant coping. This is suggestive of poor adaptation.Conclusion: University SWD experience varied levels of depression, anxiety and stress with majority of them adopting an emotion focused coping style. Continuous efforts should be made to identify psychological distress among SWDs and provide the necessary intervention to ameliorate and prevent the worsening of their challenges.